Do conscious thoughts cause behavior? [article]. - Baumeister, Roy F.
Everyday intuitions suggest full conscious control of behavior, but evidence of unconscious causation and automaticity has sustained the contrary view that conscious thought has little or no impact on behavior. We review studies with random assignment to experimental manipulations of conscious thought and behavioral dependent measures.